Race, ideology, and the polarization of America in the age of the Obama presidency - Onanga Ndjila, Blanchard (Ethics International Press Ltd, 2024)
The author contends that the 2008 election of President Barack Obama and his subsequent 2012 re-election were viewed as transformative events that should lead America into a post-modern, post-racial, and post-ideological America. That idealized vision of America turned out to be the incorrect. With the shift in demography, coupled with white American conservatives and Republicans' fear of losing America to minorities, especially to Blacks, Obama's presidency failed to transform America into a post-racial nation